Equine ovarian teratomas: Diagnostic challenges illustrated by case reports. (16th December 2021) - Duarte, L.; Allen, W. R. (Twink); Guimei, M.; Lores, M.; Wilsher, S.
Summary: Teratomas are the most common germ cell tumours to afflict the ovaries of the mare, even though they occur rarely. They are often found incidentally during routine ultrasonographic examinations of the mare's ovaries and are usually asymptomatic. Their ultrasonographic appearance varies, but they commonly present with characteristic echogenicity signs. However, before a presumptive diagnosis of a teratoma can be made, the suspect ovary, along with the rest of the reproductive tract, should be examined ultrasonographically on several occasions to confirm that the unusual structure maintains its appearance as a teratoma. This paper discusses three confirmed cases of ovarian teratoma and two cases where the ultrasonographical appearance of an ovary, combined with clinical signs, initially suggested a teratoma, but was then ruled out when the ovary had a normal appearance at subsequent examinations.